Pengaruh Kualitas Pelayanan dan Kualitas Aplikasi Terhadap Kepuasaan Pengguna Layanan Publik (Sipaduko) di Dinas Kepedudukan dan Catatan Sipil Kota Jambi - Satriyo Suryo Guritno; Novita Eka Sari; Mar Atun Saadah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
This study examines the influence of service quality and application quality on user satisfaction with the Sipaduko public service application at the Department of Population and Civil Registration of Jambi City. The research is motivated by the importance of improving the quality of digital-based public services to fulfill community needs effectively and efficiently. Although Sipaduko was developed to simplify online population administration services, several obstacles remain, including limited human resources, application usage difficulties, system disruptions, and lengthy service processes. This study uses a quantitative approach with data collected through questionnaires distributed to Sipaduko users. The data were analyzed using statistical methods to determine the partial and simultaneous effects of service quality and application quality on user satisfaction, as well as to identify the most dominant variable. The results indicate that both service quality and application quality significantly influence user satisfaction, both individually and simultaneously. Among the two variables, application quality shows the strongest influence on user satisfaction in accessing digital public services.